Early Word Order Usage in Preschool Mandarin-Speaking Typical Children and Children With Autism Spectrum Disorder: Influences of Caregiver Input? - Xu, Ying Alice; Naigles, Letitia R.; Su, Yi Esther (Frontiers in Psychology, 2022)
This study explores the emergence and productivity of word order usage in Mandarin-speaking typically-developing (TD) children and children with autism spectrum disorder (ASD), and examines how this emergence relates to frequency of use in caregiver input. Forty-two caregiver-child dyads participated in video-recorded thirty-minute semi-structured play sessions. Eleven children with ASD were matched with ten 20-month-old TD children and another eleven children with ASD were matched with ten 26-month-old TD children, on expressive language. We report four major findings: (1) Preschool Mandarin-speaking children with ASD produced word order structures with pervasive ellipsis at similar rates to language-matched TD children, but also displayed differences from TD children in their usage of SVt and VtO frames; (2) Grammatical productivity was observed in both TD children and children with ASD; moreover, children with ASD with higher expressive language produced less stereotyped language; (3) Both TD children and children with ASD heard a range of word orders in their caregivers’ input, with TD children’s input greater in amount and complexity; however, caregivers of both groups also showed no age/language-related changes in word order usage; (4) Few word-order-specific correlations emerged between caregivers and their children; however, strong correlations were observed for mean length of utterances (MLU) for both groups: Caregivers who produced longer/more complex utterances had children who did the same. Taken together, it seems that despite their pragmatic deficits, the early grammatical knowledge of word order in Mandarin-exposed children with ASD is well preserved and in general follows the typical developmental pattern. Moreover, caregiver input is broadly rather than finely tuned to the linguistic development of TD children and children with ASD, and plays a more important role in children’s general syntactic development than in specific word order acquisition. Thus, early word order usage in preschool Mandarin-speaking TD children and children with ASD may be influenced by both caregiver input and child abilities.